2018
DOI: 10.20960/nh.1696
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure is associated with age, anthropometric indicators and body composition in children with spastic cerebral palsy

Abstract: as age increased, energy expenditure also increased. The estimated energy expenditure in kcal/cm/d did not differ with age and sex. The estimated energy expenditure, based on height, would be a practical and reliable method for estimating energy expenditure and ensuring adequate nutritional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Moreover, the interpretation of body fat using % fat is also affected by low fat-free mass given the interdependency of fat and fat-free mass to estimate % fat [15]. In view of these significant limitations linked with other measurement methods, bioelectrical impedance analysis (BIA) is more and more commonly applied in assessing nutritional status recognised by clinicians monitoring nutritional status of children with CP [12,13].García Íñiguez et al showed that there is a direct correlation between resting energy expenditure, total energy expenditure and fat mass, muscle mass, and total body water in children with CP [16]. Many studies to date have also shown a relationship between energy demand and muscle tone in children with CP [2,[17][18][19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the interpretation of body fat using % fat is also affected by low fat-free mass given the interdependency of fat and fat-free mass to estimate % fat [15]. In view of these significant limitations linked with other measurement methods, bioelectrical impedance analysis (BIA) is more and more commonly applied in assessing nutritional status recognised by clinicians monitoring nutritional status of children with CP [12,13].García Íñiguez et al showed that there is a direct correlation between resting energy expenditure, total energy expenditure and fat mass, muscle mass, and total body water in children with CP [16]. Many studies to date have also shown a relationship between energy demand and muscle tone in children with CP [2,[17][18][19].…”
mentioning
confidence: 99%
“…García Íñiguez et al showed that there is a direct correlation between resting energy expenditure, total energy expenditure and fat mass, muscle mass, and total body water in children with CP [16]. Many studies to date have also shown a relationship between energy demand and muscle tone in children with CP [2,[17][18][19].…”
mentioning
confidence: 99%
“…Other authors reported lower resting energy expenditure (between 760 and 876 kcal/day) [ 123 ] and total energy expenditure of 1367 ± 329.17 kcal [ 95 ], both in younger populations. Several publications have suggested that children with bilateral spastic CP have the highest resting energy expenditure and total energy expenditure (due to the hypertonicity of the muscles), whereas children with spastic quadriplegic CP have the lowest [ 26 , 95 , 123 , 124 , 125 , 126 , 127 ]. Studies of Walker and Rieken showed a decline in the total energy expenditure with increasing GMFCS level [ 95 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cerebral palsy in children is characterized by disordered muscle tone distribution, that is, increased muscle tone (including spasticity) in lower and upper limbs and decreased muscle tone in the head–body axis (central hypotonia), limiting activity of the musculoskeletal system [ 3 , 4 ], which may disturb bone and muscle mass development in children with cerebral palsy. Previous research has shown that both body mass index (BMI) percentile and body composition in children with cerebral palsy are different from those in their healthy peers [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Results of these studies have also shown that, with a higher level of disability defined by Gross Motor Function Classification System (GMFCS) level [ 4 , 5 , 8 , 9 , 10 ], or with the most severe form of cerebral palsy [ 6 , 7 , 11 ], indices based on BMI are lower.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that both body mass index (BMI) percentile and body composition in children with cerebral palsy are different from those in their healthy peers [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Results of these studies have also shown that, with a higher level of disability defined by Gross Motor Function Classification System (GMFCS) level [ 4 , 5 , 8 , 9 , 10 ], or with the most severe form of cerebral palsy [ 6 , 7 , 11 ], indices based on BMI are lower.…”
Section: Introductionmentioning
confidence: 99%